2017
DOI: 10.1038/s41467-017-00816-w
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast giant magnetic cooling effect in ferromagnetic Co/Pt multilayers

Abstract: The magnetic cooling effect originates from a large change in entropy by the forced magnetization alignment, which has long been considered to be utilized as an alternative environment-friendly cooling technology compared to conventional refrigeration. However, an ultimate timescale of the magnetic cooling effect has never been studied yet. Here, we report that a giant magnetic cooling (up to 200 K) phenomenon exists in the Co/Pt nano-multilayers on a femtosecond timescale during the photoinduced demagnetizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…G ee is an energy exchange coefficient between non-thermal and thermal electrons. The K l term describes the thermal diffusion of energy via the lattice, which is modeled to be proportional to the third power of the temperature increase of the lattice system 12,33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…G ee is an energy exchange coefficient between non-thermal and thermal electrons. The K l term describes the thermal diffusion of energy via the lattice, which is modeled to be proportional to the third power of the temperature increase of the lattice system 12,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Photoinduced spin dynamics allows us to control magnetic moments on a femtosecond time scale simply by optical pulses 4,5 , as well as by external field or spin current 6,7 . Since the seminal work on a Ni single layer by Beaurepaire et al 8 , numerous studies have investigated the underlying mechanism of ultrafast photoinduced spin dynamics [9][10][11][12][13] . It has been generally accepted that energy from photons is transferred first into the electron sub-system within a few tens of femtoseconds and hot electrons then transfer their energies into the spin and the lattice sub-systems, leading to a final equilibrium state among electron, spin, and lattice sub-systems [8][9][10] .…”
mentioning
confidence: 99%
“…Such spin cooling and spin heating of magnetization can be observed when the external source of angular momentum is a magnetic field 23 , spin-polarized hot electrons 24 26 , the spin angular momentum coming from one sublattice in ferrimagnets 27 29 or a Ruderman–Kittel–Kasuya–Yosida (RKKY) exchange coupling 30 , 31 . In these cases, however, magnetization was either far from quenched or CSD was still present (see the supporting information in ref.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] One of the key issues related to the ultrafast spin dynamics of magnetic materials is the demagnetization process. In the transition 3d ferromagnetic metals, [5][6][7][8] the magnetic order was found to be quenched in a sub-picosecond timescale and then re-magnetized in a longer timescale of several picoseconds (ps). In half metals, [9][10][11] such as Sr2FeMoO6, CrO2 and La0.6Sr0.4MnO3, experimental observations have shown that the ultrafast demagnetization involves two steps: an initial instantaneous decrease within a ps and a subsequent slow decreasing response lasting for several hundreds of ps.…”
mentioning
confidence: 99%
“…However, the transient enhancement of the magnetization observed with s-polarized probe light cannot be expected from the thermal process, which should lead to an instantaneous drop rather than increase in magnetization as previously reported. [8] Considering the strongly coupled degrees of freedom between the spin and orbital in the LSMO film, we expect that the orbital orientation plays a role in the magnetization enhancement. To verify this assumption, we have investigated the effect of the probe light polarization orientation on the pump-induced spin dynamics.…”
mentioning
confidence: 99%